Сучасний стан та перспективи розвитку колекції роду Ficus L. (Moraceae Link.) в оранжереях Національного ботанічного саду ім. М.М. Гришка НАН України - Kykavska, N.I. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2014)
The data about modern state and history of foundation of genus Ficus L. collection in M.M. Gryshko National Botanical Garden of the NAS of Ukraine are given. The taxonomic compounds of Ficus collection in NBG and sourses of replessishment are analyzed. The data about geographical distribution of ficuses is considered. Most of the collection are representing ficuses from South-East Asia, there are endemics from Australia and species that are entered in Red lists of the International Union for Conservation of Nature. The data about phonological phases of ficuses in greenhouses are presented. Observed the formation of inflorescences at the greenhouses conditions mainly for ficuses native from South-East Asia, when ficuses native from Africa, India, Australia, South America and Middle East rarely form the inflorescence. Prospects of development of collection and tendencies of study of genus Ficus species in Botanical Garden are elucidated.